Reviving Architectural Heritage: Restorations and Cultural Implications of the Jome Mosque in Kukon: Menghidupkan Warisan Arsitektur: Restorasi dan Implikasi Budaya Masjid Jome di Kukon - Iskanderov Sultanbek (Universitas Muhammadiyah Sidoarjo, 2023)
This study examines the historical renovations and cultural implications of the Jame Mosque in Kukon, a significant architectural monument. Through an analysis of various accounts from historical works such as